Isolation and identification of cadmium-reducing bacteria from contaminated coastal sediment in the Northern Coast of Indramayu, Indonesia - Tri Dewi Kusumaningrum Pribadi; Buntora Pasaribu; Kalysta Fellatami; Jiang Mingguo; Azimah Ismail; Choerunnisa Febriani; Ching Fui Fui @ Faihana Ching Abdullah; Yudi Nurul Ihsan (Asian Network for Scientific Information, 2025)
Background and Objective: Cadmium (Cd) is one of the heavy metal pollutants and its accumulation impacts the sustainability of marine organisms. Current research aimed to isolate and identify the cadmium-reducing bacteria from contaminated coastal sediment in Karangsong Port, Indramayu, Indonesia. The isolates were investigated for their potential to reduce cadmium and showed the cadmium reduction drastically up to 50% at 6 hrs treated under different cadmium concentrations of 0, 5, 1 and 1.5 ppm, respectively. Materials and Methods: Morphological characteristics were observed in most of the isolates. Out of 8 isolates, two selected strains such as Karangsong Cd 3 and Cd 7 were identified by 16S rRNA sequencing as Pseudoalteromonas issachenkonii strain KMM 3549 (Acc. No. NR 025139.1) and Pseudoalteromonas tetraodonis GFC strain IAM 14160 (Acc. No. NR 041787.1), respectively. Results: The cadmium resistance profile showed that the selected isolates were resistant to various concentrations of cadmium (Cd). The isolates reduced the concentration of cadmium drastically up to 50% at 6 hrs. The results demonstrated the two bacteria are possible to remove the cadmium from seawater containing cadmium. The gram staining showed bacterial colony morphology were diplobacilli and coccobacillus. Conclusion: These results suggested that the Karangsong Cd 3 and Cd 7 could facilitate the new references of future microbial applications for bioremediation efforts.